2005
DOI: 10.1128/iai.73.5.3096-3103.2005
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Genetic Diversity of Group BStreptococcusCapsular Polysaccharides

Abstract: Group B Streptococcus (GBS) is an important pathogen of neonates, pregnant women, and immunocompromised individuals. GBS isolates associated with human infection produce one of nine antigenically distinct capsular polysaccharides which are thought to play a key role in virulence. A comparison of GBS polysaccharide structures of all nine known GBS serotypes together with the predicted amino acid sequences of the proteins that direct their synthesis suggests that the evolution of serotype-specific capsular polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
179
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 38 publications
4
179
0
5
Order By: Relevance
“…However, the kind of PS structure important for their activity and how these molecules exert their activities on host cells are still open questions. In addition, it has been shown that extracellular PSs of Streptococcus thermophilus (39) and group B Streptococcus capsular PSs are highly diverse (6). It is well-known that pathogenic bacteria, such as hemolytic streptococci, often change their outer surface glycan profile to escape the host immune defense mechanism (5).…”
mentioning
confidence: 99%
“…However, the kind of PS structure important for their activity and how these molecules exert their activities on host cells are still open questions. In addition, it has been shown that extracellular PSs of Streptococcus thermophilus (39) and group B Streptococcus capsular PSs are highly diverse (6). It is well-known that pathogenic bacteria, such as hemolytic streptococci, often change their outer surface glycan profile to escape the host immune defense mechanism (5).…”
mentioning
confidence: 99%
“…The relatively low rate of recombination among ST-1 strains allowed for elucidation of discrete GBS loci under positive selection, only some of which have been previously identified as important for GBS host-pathogen interaction (22,26,35). Thus, in conjunction with our Alp findings, these data provide a new platform for investigating why ST-1 GBS strains have emerged as a major cause of invasive disease in nonpregnant adults, such as analysis of the previously unstudied TCS encoded by rdf_0314-0315.…”
Section: Discussionmentioning
confidence: 99%
“…To compare with previously published primer pairs for serotype II-, VII-and VIII-specific PCRs (Borchardt et al, 2004;Cieslewicz et al, 2005) we used cpsIIK, cpsVIIM and cpsVIIIJ, respectively, rather than cpsH as the targets for primers and probes (Kong et al, 2002). We also designed one GBS-specific primer pair and two GBSspecific probes (Ke & Bergeron, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Nine GBS capsular polysaccharide serotypes and corresponding capsular polysaccharide synthesis (cps) gene clusters are recognized (Cieslewicz et al, 2005). Their distribution varies according to geographic location and study population (Schuchat, 1998).…”
Section: Introductionmentioning
confidence: 99%